Economics of mental well-being: a prospective study estimating associated health care costs and sickness benefit transfers in Denmark - Santini, Ziggi Ivan (Eur J Health Econ, 2021)
BACKGROUND: Previous literature has examined the societal costs of mental illness, but few studies have estimated the costs associated with mental well-being. In this study, a prospective analysis was conducted on Danish data to determine 1) the association between mental well-being (measured in 2016) and government expenditure in 2017, specifially healthcare costs and sickness benefit transfers. METHODS: Data stem from a Danish population-based survey of 3,508 adults (aged 16 + years) in 2016, which was linked to Danish registry data. A validated scale (WEMWBS) was used for the assessment of mental well-being. Costs are expressed in USD PPP. A two-part model was applied to predict costs in 2017, adjusting for sociodemographics, health status (including psychiatric morbidity and health behaviour), as well as costs in the previous year (2016). RESULTS: Each point increase in mental well-being (measured in 2016) was associated with lower healthcare costs ($− 42.5, 95% CI = $− 78.7, $− 6.3) and lower costs in terms of sickness benefit transfers ($− 23.1, 95% CI = $− 41.9, $− 4.3) per person in 2017. CONCLUSIONS: Estimated reductions in costs related to mental well-being add to what is already known about potential savings related to the prevention of mental illness. It does so by illustrating the savings that could be made by moving from lower to higher levels of mental well-being both within and beyond the clinical range. Our estimates pertain to costs associated with those health-related outcomes that were included in the study, but excluding other social and economic outcomes and benefits. They cover immediate cost estimates (costs generated the year following mental well-being measurement) and not those that could follow improved mental well-being over the longer term. They may therefore be considered conservative from a societal perspective. Population approaches to mental health promotion are necessary, not only to potentiate disease prevention strategies, but also to reduce costs related to lower levels of mental well-being in the non-mental illness population. Our results suggest that useful reductions in both health care resource use and costs, as well as in costs due to sick leave from the workplace, could be achieved from investment in mental well-being promotion within a year.